Antithrombotic Therapy in Atrial Fibrillation Associated with Valvular Heart Disease: Executive Summary of a Joint Consensus Document from the European Heart Rhythm Association (EHRA) and European Society of Cardiology Working Group on Thrombosis, Endorsed by the ESC Working Group on Valvular Heart Disease, Cardiac Arrhythmia Society of Southern Africa (CASSA), Heart Rhythm Society (HRS), Asia Pacific Heart Rhythm Society (APHRS), South African Heart (SA Heart) Association and Sociedad Latinoamericana de Estimulación Cardíaca y Electrofisiología (SOLEACE) - Lip, Gregory Y. H.; Collet, Jean Philippe; de Caterina, Raffaele; Fauchier, Laurent; Lane, Deirdre A.; Larsen, Torben B.; Marin, Francisco; Morais, Joao; Narasimhan, Calambur; Olshansky, Brian; Pierard, Luc; Potpara, Tatjana; Sarrafzadegan, Nizal; Sliwa, Karen; Varela, Gonzalo; Vilahur, Gemma; Weiss, Thomas; Boriani, Giuseppe; Rocca, Bianca (Thrombosis and Haemostasis, 2017)
Management strategies for patients with atrial fibrillation (AF) in association with valvular heart disease (VHD) have been less informed by randomized trials, which have largely focused on ‘non-valvular AF’ patients. Thromboembolic risk also varies according to valve lesion and may also be associated with CHA2DS2-VASc score risk factor components, rather than only the valve disease being causal.Given the need to provide expert recommendations for professionals participating in the care of patients presenting with AF and associated VHD, a task force was convened by the European Heart Rhythm Association (EHRA) and European Society of Cardiology (ESC) Working Group (WG) on Thrombosis, with representation from the ESC WG on Valvular Heart Disease, Heart Rhythm Society (HRS), Asia Pacific Heart Rhythm Society (APHRS), South African Heart (SA Heart) Association and Sociedad Latinoamericana de Estimulación Cardíaca y Electrofisiología (SOLEACE) with the remit to comprehensively review the published evidence, and to produce a consensus document on the management of patients with AF and associated VHD, with up-to-date consensus statements for clinical practice for different forms of VHD, based on the principles of evidence-based medicine.This is an executive summary of a consensus document which proposes that the term ‘valvular AF’ is outdated and given that any definition ultimately relates to the evaluated practical use of oral anticoagulation (OAC) type, we propose a functionalEHRA (Evaluated Heartvalves, Rheumatic or Artificial) categorization in relation to the type of OAC use in patients with AF, as follows: (1) EHRA (Evaluated Heartvalves, Rheumatic or Artificial) type 1 VHD, which refers to AF patients with ‘VHD needing therapy with a vitamin K antagonist (VKA)’ and (2) EHRA (Evaluated Heartvalves, Rheumatic or Artificial) type 2 VHD, which refers to AF patients with ‘VHD needing therapy with a VKA or a non-VKA oral anticoagulant also taking into consideration CHA2DS2-VASc score risk factor components.
Keywords: atrial fibrillation; valvular heart disease; mitral stenosis; mechanical prosthetic heart valves; thromboembolism; stroke; stroke prevention; anticoagulation; vitamin K antagonists; NOACs